Potential of Y. lipolytica epoxide hydrolase for efficient production of enantiopure (R)-1,2-octanediol - Vijaya P. Godase; V. Ravi Kumar; Ameeta Ravi Kumar (AMB Express, 2023)
Abstract The recombinant Yleh from a tropical marine yeast Yarrowia lipolytica NCIM 3589 exhibited a high epoxide hydrolase activity of 9.34 ± 1.80 µmol min-1 mg-1 protein towards 1,2-epoxyoctane (EO), at pH 8.0 and 30 °C. The reaction product was identified as 1,2-Octanediol (OD) by GC-MS using EO and H2O18 as substrate, affirming the functionality of Yleh as an epoxide hydrolase. For EO, the K m, V max, and k cat/K m values were 0.43 ± 0.017 mM, 0.042 ± 0.003 mM min-1, and 467.17 ± 39.43 mM-1 min-1, respectively. To optimize the reaction conditions for conversion of racemic EO by Yleh catalyst to enantiopure (R)-1,2-octanediol, initially, Response Surface Methodology was employed. Under optimized reaction conditions of 15 mM EO, 150 µg purified Yleh at 30 °C a maximal diol production of 7.11 mM was attained in a short span of 65 min with a yield of 47.4%. Green technology using deep eutectic solvents for the hydrophobic substrate (EO) were tested as co-solvents in Yleh catalyzed EO hydrolysis. Choline chloride-Glycerol, produced 9.08 mM OD with an increased OD yield of 60.5%. Thus, results showed that deep eutectic solvents could be a promising solvent for Yleh-catalyzed reactions making Yleh a potential biocatalyst for the biosynthesis of enantiopure synthons.